Laparoscopic removal of a 40-cm paratubal cyst in a morbidly obese patient - Luay Ibrahim Abu Atileh; Duaa Dahbour; Hasan Hammo; Mai Abdullattif (Wolters Kluwer Medknow Publications, 2020)
Paratubal cysts (PTCs) are remnants of the paramesonephric or the mesonephric ducts that are present during embryogenesis. They are mostly benign; however, malignancy has been described. The incidence of PTCs is estimated to be 5%-20% of all adnexal masses. They can present in any age group but most commonly the third or fourth decades. Huge PTCs exceeding 10-15 cm in diameter are considered rare and challenging, as only a few cases have been reported that describe complete laparoscopic excision. A simple asymptomatic PTC can be managed expectantly; however, surgery is mandatory if the cyst is huge, complicated, or causes severe symptoms. In this article, we describe a laparoscopic removal of a 40-cm PTC in a 32-year- old woman, as the largest PTC in literature that was removed by laparoscopy.